Permukiman di Lingkungan Danau Catatan Atas Hasil Penelitian Situs-situs Ranu di Jawa Timur - Gunadi Kasnowihardjo (Balai Arkeologi Sumatera Utara, 2010)
AbstractLake area, such as Ranu Klakah, Ranu Gedang and Ranu Segaran, is the past settlements area which occupied by people since the neolithic period which were marked by the use of square pickaxe artifact. Activity in ranu region continue until the next period which is characterized by the existence of megalithic monuments, the remains of an old temple, and tomb from the early days of the entry of Islam, even now, the location of ancient settlements are still used as a residential location